UML-Based Web Engineering Untuk Perancangan Aplikasi - Ester Lumba; Yulius Denny Prabowo (Sekolah Tinggi Ilmu Komputer YOS SUDARSO Purwokerto, 2016)
Submission of thesis proposals is often constrained by the problem of time compatibility between students and the head of the study program. The development of technology, especially the internet, should be used to overcome this problem. This study aims to build a web-based thesis proposal submission application. The development of a web-based thesis proposal submission application is carried out using the UML-based Web Engineering (UWE) method. The result of this research is a web-based thesis proposal submission application that can be used by admins, heads of study programs and students. In this application, students can submit a proposal by filling out the submission form in accordance with the specified period. Proposals submitted by students will be grouped by study program. Proposals submitted have three statuses, namely correct, accepted or rejected. Students can see the status of the proposals submitted after being checked by the head of the study program. In the application there is a thesis proposal submission log. After the proposal is received, the proposal submission form cannot be accessed. The results of this study can be accessed at the address http://www.risetdosen.net/. Keywords: thesis, proposal, UWE, student